The Effect of STEM Integrated PBL Model to Practice Students' Scientific Communication Skills - Ayu Islamiyah; Fitria Eka Wulandari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to determine the effect of the STEM integrated PBL model to practice students' scientific communication skills. The population of this study were students from the eighth grade of Junior High School of 1 Candi. The sample used is 30 students selected from the population using simple random sampling technique. This research method is Pre-Experimental Design. The design in this study is a one-shot case study. Data from the observation results of the assessment of students' scientific communication skills were analyzed using quantitative descriptive methods, by finding the mean and finding the percentage of indicators of scientific communication skills. The results showed that the application of the STEM-integrated PBL model in science learning material additives was able to improve students' scientific communication skills in a good category, with the average result of students' scientific communication being 2.7.